TYPOLOGY OF AUXILIARY VERBS IN ENGLISH AND UZBEK (Web of Teachers: Inderscience Research, 2024)
This article provides a comprehensive comparison of auxiliary verbs in English and Uzbek, two languages with distinct typological features. Through an analysis of literature and empirical data, it examines the morphosyntactic properties, semantic roles, and grammatical functions of auxiliary verbs in both languages. The study employs a comparative framework to highlight similarities and differences, shedding light on how these linguistic structures reflect the underlying grammatical systems of English and Uzbek. The findings contribute to our understanding of typological variation and language-specific patterns in auxiliary verb usage.